Pediatric Capacity Building in Northern Laos: An Evaluation of the Pediatric Nursing Training Program at Lao Friends Hospital for Children - Rebecca Silvers; Maly Chittaphai; Matt Evans; Jessica Van Meter (PLoS ONE, 2026)
Background In 2015, the child mortality rate in Laos was 53.6 per 1,000 live births. The Lao Friends Hospital for Children (LFHC) in Luang Prabang was established to enhance access to specialized pediatric care. To support workforce development, a Pediatric Nursing Training Program was implemented. However, the program has not undergone a formal evaluation since its inception. This study aims to evaluate the program’s first five years. Study design The evaluation included a review of curriculum documents via an online platform and feedback collection through an online survey administered to former expatriate nurse volunteers who provided clinical mentorship. Additionally, semi-structured interviews were conducted with former nurse leaders who designed and implemented the program. Qualitative data were analyzed thematically and validated through triangulation. Results The curriculum review revealed system-based and course-specific plans, including clear objectives, teaching methods, and evaluation tools. Of the 148 clinical mentors surveyed, a 45% response rate was achieved. Survey responses indicated improvements in nurses’ clinical skills since the program’s inception, with mentors emphasizing the importance of cultural attunement to Lao staff. Six out of seven former nurse leaders participated in interviews. Key themes emerged, highlighting the value of culturally relevant educational materials, multimodal teaching strategies, a train-the-trainer approach, and clinical mentorship as integral components of the program. Conclusion The development of pediatric nursing specialization at LFHC was facilitated by structured curriculum plans, cultural sensitivity, diverse teaching methodologies, and robust clinical mentorship. These findings provide valuable insights for designing culturally competent and sustainable training programs in Laos and similar contexts.